High order spectral analysis of ferroresonance phenomena in electric power systems - AKGÜN, ÖMER (My University, 2023)
This study presents a comprehensive investigation of ferroresonance, a dangerous electrical phenomenon that poses significant financial risks. Using real electrical transmission line parameters, we simulated synthetic ferroresonance scenarios on a model and analyzed the resulting data using high-order spectral analysis methods, including the Wigner-Ville method, Welch method, frequency-power analysis, and spectral methods. Our analysis revealed changes in frequency and power before and after ferroresonance, with third and fourth-order cumulants being calculated. We confirmed the accuracy of the power transmission line’s base frequency and power before the ferroresonance event and determined the frequency and power values before and after ferroresonance with frequency-power analysis. Our cumulative analysis results showed symmetrical results that are consistent with the properties of ferroresonance. Additionally, we found that the Wigner Ville method’s high-resolution results were significantly more effective than conventional methods. Our study’s findings provide valuable insights into ferroresonance’s behavior and may inform the development of more effective prevention and mitigation strategies.
Keywords: Bilgisayar Bilimleri; Mühendislik ve Teknoloji; Computer Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; Mühendislik; Malzeme Bilimi; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; ENGINEERING; MATERIALS SCIENCE; Genel Bilgisayar Bilimi; Fizik Bilimleri; Genel Malzeme Bilimi; Genel Mühendislik; General Computer Science; Physical Sciences; General Materials Science; General Engineering; Comulant; electric power system; ferroresonance; Ferroresonance; Harmonic analysis; high order spectral analysis; Mathematical models; Power systems; Power transmission lines; Spectral analysis; Time-frequency analysis; wigner-ville; Comulant; electric power system; ferroresonance; high order spectral analysis; wignerville